Honey Bees Avoid Nectar Colonized by Three Bacterial Species, But Not by a Yeast Species, Isolated from the Bee Gut - Good, Ashley P.; Gauthier, Marie-Pierre L.; Vannette, Rachel L.; Fukami, Tadashi (PloS one, 2014)
The gut microflora of the honey bee, Apis mellifera, is receiving increasing attention as a potential determinant of the bees' health and their efficacy as pollinators. Studies have focused primarily on the microbial taxa that appear numerically dominant in the bee gut, with the assumption that the dominant status suggests their potential importance to the bees' health. However, numerically minor taxa might also influence the bees' efficacy as pollinators, particularly if they are not only present in the gut, but also capable of growing in floral nectar and altering its chemical properties. Nonetheless, it is not well understood whether honey bees have any feeding preference for or against nectar colonized by specific microbial species. To test whether bees exhibit a preference, we conducted a series of field experiments at an apiary using synthetic nectar inoculated with specific species of bacteria or yeast that had been isolated from the bee gut, but are considered minor components of the gut microflora. These species had also been found in floral nectar. Our results indicated that honey bees avoided nectar colonized by the bacteria Asaia astilbes, Erwinia tasmaniensis, and Lactobacillus kunkeei, whereas the yeast Metschnikowia reukaufii did not affect the feeding preference of the insects. Our results also indicated that avoidance of bacteria-colonized nectar was caused not by the presence of the bacteria per se, but by the chemical changes to nectar made by the bacteria. These findings suggest that gut microbes may not only affect the bees' health as symbionts, but that some of the microbes may possibly affect the efficacy of A. mellifera as pollinators by altering nectar chemistry and influencing their foraging behavior.